Pengaruh Pengalaman Auditor dan Profesionalisme Auditor terhadap Pendeteksian Kecurangan Audit - Sairun Simanullang; Fransiska Simanullang (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the influence of auditor experience and professionalism on the ability to detect audit conditions in Public Accounting Firms (KAP) in South Jakarta. The background of this study is based on the important role of auditors in ensuring the integrity of financial statements and preventing financial practices that can harm various parties, including investors, shareholders, and regulators. In an increasingly complex business world, layout practices are increasingly difficult to detect without adequate professional skills. Therefore, factors such as auditor experience and professionalism are crucial in supporting audit quality. This study used a survey method with a questionnaire instrument distributed to auditors working at several KAPs in the study area. The collected data were analyzed using Statistical Package for the Social Sciences (SPSS) software to test the proposed hypotheses. The results showed that auditor experience significantly influenced the ability to detect audit conditions, indicating that the greater the auditor's work experience, the sharper their ability to identify indications of conditions. In addition, auditor professionalism was also proven to have a positive effect on the detection of audit conditions. Aspects such as responsibility, objectivity, competence, and commitment to professional ethics are important foundations for an effective and independent audit process. These findings indicate that integrity, responsibility, and adherence to professional standards are important factors supporting audit effectiveness. This research is expected to serve as a reference for public accounting firms (KAPs) in improving audit quality through competency development, ongoing training, and upholding auditor professional ethics in the workplace. This study also recommends the need for ongoing training to increase auditor sensitivity to increasingly complex conditions.